Power quality improvement using multilevel inverter-based active filter for medium-voltage high-power distribution system: a comprehensive review. (29th July 2021) - Ray, Soumyadeep; Gupta, Nitin; Gupta, R.A.
Medium-voltage distribution system faces great challenges as the number of high-power loads is increasing which inject nonlinearity into the grid. On the other side, sinusoidal and uninterrupted voltage and current waveform at rated frequency is highly desirable at the consumer end. Two-level inverter-based active filter is facing great challenges in medium-voltage distribution network due to the use of high rating switching devices and use of a line-frequency transformer. Multilevel inverter (MLI) posses a great solution in such scenario as it generates higher voltage output with lower rating switching devices. MLI technology is widely accepted in medium to high-voltage industrial applications. Therefore, this paper presents a widespread review on MLI-based active filter (AF) by assessing its potential to replace two-level inverter-based AF in medium-voltage distribution sector. Different possible configurations, control techniques and their different applications are reviewed comprehensively. A list of 78 research papers is decisively examined and is appended for quick reference.